DIAGNOSTIC VALUE OF SPECIFIC IMMUNE COMPLEXES IN DETECTION OF ACTIVE TUBERCULOSIS INFECTION - A. A. Starshinova; E. V. Istomina; Yu. S. Zinchenko; M. V. Filatov; S. B. Landa; V. S. Burdakov; E. N. Belyaeva; M. M. Nazarenko; N. V. Sapozhnikova; M. V. Pavlova; P. K. Yablonskiy (Медицинская иммунология)
The diagnostic of tuberculosis infection, including the use of immunological methods, evolved significant changes. The introduction of new diagnostic tests allowed to improve the diagnosis of latent tuberculosis infection (LTI). However, the positive results of immunological tests in both tuberculosis patients and in those with LTI do not allow to divide these conditions, which requires the development and implementation of new diagnostic approaches.Materials and methods. A prospective study with a survey of two groups of patients was conducted: group I (n=50) - patients with verified pulmonary tuberculosis, MBT (+); group II (n =15) – subjects with LTI and control group – healthy subjects (n=14). The examination complex included clinical, radiological, bacteriological, immunological (Mantoux test with 2 TU, T-SPOT.TB, QFT and Diaskintest) methods. Immune complexes were determined in all patients and healthy individuals by the method of dynamic light scattering after the in vitro addition of specific antigens - peptides ESAT-6 and SFP-10.Results. The obtained data demonstrate the low informativeness of the clinical method in the diagnostic of pulmonary tuberculosis. In the presence of characteristic X-ray changes, bacteriological verification of tuberculosis was obtained only in 46% of cases. The use of various immunological tests allows to obtain positive test results in 84-90% of cases simultaneously with the 100% of the positive results in subjects with LTI. Determination of specific immune complexes by the method of dynamic light scattering allows to determine the activity of tuberculosis infection in 100 % of cases and to identify a high-risk group for the development of active tuberculosis in people with latent tuberculosis infection.Conclusions: the obtained data can be applied not only in the diagnosis of active tuberculosis in the absence of diagnosis verification, but also allow to identify a high-risk group for the development of the disease in people with latent tuberculosis infection.